Soy-based infant nutrition: a review - Yvan Vandenplas; Badriul Hegar (Paediatrica Indonesiana, 2014)
Dietary consumption of soy varies worldwide.In Asia, people traditionally consume largequantities of soy, while in Europe, soy is notpart of the traditional or daily eating habits.The USA is a major soy producer. The mean intake ofisoflavones by an adult is 8 - 50 mg/day in Asia but only0.5 - 3.5 mg/day in the Western world.1 The soy intakeof a vegetarian is 3 - 12 mg/day and a vegan achievesan intake of 15-60 mg/day.2In the early 1900s, soy-protein preparationswere the only option for the treatment of cow's milkprotein allergy (CMPA) . The first report of the use ofa soybean -based formula for infants dates from 1909.3Most soy drinks are not enriched with zinc, iron,calcium, phosphorous, methionine, or carnitine. Soydrinks also do not contain soy isolate. Soy productsthat do not fulfill the criteria to be an infant formulaare not adapted for infant feeding.